2017
DOI: 10.1213/ane.0000000000002434
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Efficacy of Systemic Opioid-Sparing Analgesics in Pediatric Surgical Populations: A Systematic Review

Abstract: While a large number of studies has examined the efficacy of opioid-sparing analgesics in adult surgical populations, fewer studies are available to guide postoperative pain treatment in pediatric patients. We systematically reviewed available publications on the use of systemic nonopioid agents for postoperative analgesia in pediatric surgical populations. A comprehensive literature search identified meta-analyses and randomized controlled trials (RCTs) assessing the effects of systemic, nonopioid agents on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 61 publications
0
50
0
1
Order By: Relevance
“…Despite its attractive analgesic profile, ketamine has been postulated to trigger undesired augmentation of systemic hemodynamics, PONV, and psychomimetic manifestations, with hallucinations being the predominant one among them . Yet, a bulk of evidence demonstrates that the risk of the aforementioned side‐effects becomes trivial when analgesic doses of ketamine (<2 mg/kg) are applied . Our results showed that the combined use of pre‐incisional infiltration of tramadol with local or intravenous ketamine provided better postoperative pain control and quality of recovery than using each drug separately, with minor adverse effects .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Despite its attractive analgesic profile, ketamine has been postulated to trigger undesired augmentation of systemic hemodynamics, PONV, and psychomimetic manifestations, with hallucinations being the predominant one among them . Yet, a bulk of evidence demonstrates that the risk of the aforementioned side‐effects becomes trivial when analgesic doses of ketamine (<2 mg/kg) are applied . Our results showed that the combined use of pre‐incisional infiltration of tramadol with local or intravenous ketamine provided better postoperative pain control and quality of recovery than using each drug separately, with minor adverse effects .…”
Section: Discussionmentioning
confidence: 68%
“…Although the CHEOPS constitutes a reliable and widely implemented clinical practice pain intensity tool for pediatric populations, it mainly relies on behavioral expression. This implies that the CHEOPS actually measures pain in an indirect manner as it indicates the intensity of pain‐related distress and pain reactivity rather than the intensity of pain …”
Section: Discussionmentioning
confidence: 99%
“…There is meta-analytical evidence on the opioid-sparing effects of paracetamol administration to treat post-operative or posttraumatic pain in adults and in children. In contrast, the demonstration of a clinically significant reduction in opioidrelated adverse effects (like sedation and nausea) is much less robust (48,49). In contrast, data in neonatal cohorts on paracetamol-related opioid-sparing effects in neonates were only more recently reported in two different cohorts (surgical and medical intensive care, respectively).…”
Section: Paracetamol and Opioid-sparing Effects In Major Pain Syndrommentioning
confidence: 99%
“…Postoje dokazi, mada ograničeni, da perioperativno primenjen paracetamol, nesteroidni antiinflamatorni lekovi, deksametazon, ketamin, klonidin i deksmedetomidin mogu umanjiti postoperativni bol i potrošnju opioida u nekim populacijama pedijatrijskih hirurških bolesnika (71). Nedavno je sprovedena metaanaliza deset randomizovanih kontrolisanih studija (sa ukupno 665 učesnika) koje su ispitivale uticaj intravenski primenjenog magnezijum-sulfata na postoperativne komplikacije kod dece koja su podvrgnuta tonzilektomiji (72).…”
Section: Intravenska Primena Magnezijum-sulfata Kod Ljudiunclassified